Preliminary psychometric validation of the multidimensional inventory of sport excellence: attention scales and mental energy - Sindik, J.; Botica, A.; Fiškuš, M. (Montenegrin Journal of Sports Science and Medicine, 2015)
Sport psychologist needs to understand how psychological factors affect athletic performance of an individual, considering individual differences among athletes. Each specific problem in working with athletes must be considered depending on complex factors: the type (specificity) of sport; characteristics of the activity (the training or competition); stages of athletes` sports development; gender and age differences, etc. Although there are numerous psychological instruments, which assess psychological characteristics of athletes, it is important to select instruments adjusted to athletes, working style of sports psychologist, available time and other constraints. Here, we have formulated a preliminary version of our own battery of questionnaires, named Multidimensional Inventory of Sport Excellence (MUSI), selecting the items for following psychological characteristics: energizing, maintaining attention, directing attention, wide internal / external attention and narrow internal / external attention. In this phase of the study, participants were stratified only by gender. Sample of 248 participants was examined, of which 103 male athletes (age 24.52 ± 11.80 years) and 145 female athletes (age 16.61 ± 6.69 years), from the Croatian sports clubs, competing in 16 different sports (archery, football, handball, bocce, bowling, cycling, karate, rowing, tennis, volleyball, basketball, synchronized swimming, triathlon, table tennis, chess, badminton). Data were collected from March to June 2014 in Rijeka, during the trainings in sports clubs. Results of Principal Component Analysis and the reliabilities type internal consistency showed that each of sub-questionnaires from battery MUSI have satisfactory reliability and construct validity, giving positive guidance for future adaptation of the questionnaire to specific subpopulations of athletes.